Interpreting sperm DNA damage in a diverse range of mammalian sperm by means of the two-tailed comet assay - Cortés-Gutiérrez, Elva I.; López-Fernández, Carmen; Fernández, José Luis; Dávila-Rodríguez, Martha I.; Johnston, Stephen D.; Gosálvez, Jaime (Frontiers in Genetics, 2014)
Sperm DNA damage is associated with fertilization failure, impaired pre-and post- embryo implantation and poor pregnancy outcome. A series of methodologies to assess DNA damage in spermatozoa have been developed but most are unable to differentiate between single-stranded DNA breaks (SSBs) and double-stranded DNA breaks (DSBs) on the same sperm cell. The two-dimensional Two-Tailed Comet assay (TT-comet) protocol highlighted in this review overcomes this limitation and emphasizes the importance in accounting for difference in sperm protamine composition at a species-specific level for the appropriate preparation of the assay. The TT-comet is a modification of the original comet assay that uses a two dimensional electrophoresis to allow for the simultaneous evaluation of relatively high numbers of DSBs and SSBs in mammalian spermatozoa. Here we have compiled a retrospective overview of how the TT-comet assay has been used to investigate the structure and function of sperm DNA across a diverse range of mammalian species (eutheria, metatheria and prototheria). When conducted as part of the TT-comet assay, we discuss how (a) the alkaline comet single assay has been used to help understand the constitutive and transient changes in DNA structure associated with chromatin packing, (b) the capacity of the TT-comet to differentiate between the presence of SSBs and DSBs (c) and the possible implications of SSBs or DSBs for the assessment of infertility.